Hasmi Novianti PENGGUNAAN MAJAS DALAM PUISI MENGGUNAKAN MEDIA LAGU SISWA KELAS VIII SMP NEGERI 4 SATU ATAP SUNGAI LIKU KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Novianti, Hasmi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT Poetry is a literary genre that is interesting to observe in addition to prose and drama. As one genre of literature, of course, poetry can use the language as a medium. Through poetry, the author freely express their feelings and imagination to set forth in a paper aesthetic value. As one literary genre that uses language meaningful connotations, in the poetry of many languages ​​bermajas found useful to add to the aesthetic value of the work. This study aimed to describe the type of figure of speech what are contained in the poem by media songs written by the students of class VIII.5 SMP N 4 One Roof Meander River District of Sphere Coastal South Coastal District. This research is a qualitative study using descriptive methods. Samples were VIII.5 grade students of SMP N 4 One Roof Meander River District of Sphere Coastal South Coastal District with the number of students 30 people. This research data is the result of the test write poetry using the medium of songs written by the sample. The test used is a test to measure the performance poetry writing skills test to see figure of speech. Data that has been analyzed by the steps as follows: (1) read poems by students, (2) identification data based on sample code and the title poem of students, (3) classifying the type of figure of speech contained in poetry by students, (4) identify the figure of speech that predominantly used in poetry by students, (5) analyze the figure of speech written by the students using the media track, (6) summed up the results of the data analysis. Based on the results, it can be concluded that the figure of speech contained in the poem VIII.5 grade students of SMP N 4 One Roof Meander River District of Sphere Coastal South Coastal District broadly grouped into four, namely the comparative figure of speech, opposition, interlacing and looping. Consist of a comparison figure of speech figure of speech personification of use and figure of speech parable 15 17 use. Majas opposition consists of the use of hyperbole and litotes 7 4 use. Majas linkage consists of sinekdoke 1 use, allusion 9 use and inversion one use. Majas iteration consists of one use of alliteration and repetition 9 use. Key words: Majas, Song Media, Poetry